Mini-review: Processed red meat intake and risk of neurodegenerative diseases - Chen, Ke-qian; Cao, Wen-jin; Liu, Zheng; Liu, Ren-zhu (Frontiers in Nutrition, 2025)
Neurodegenerative diseases (NDDs) are a group of disorders characterized by the progressive loss of neurons in specific areas of the central nervous system. In recent years, more and more research has focused on the influence of diet on NDDs. As a common food, processed red meat is widely consumed worldwide. Many studies have shown that processed red meat may increase the risk of cancer, diabetes and cardiovascular disease. Unfortunately, it is unclear whether processed red meat affects NDDs. Therefore, we reviewed the existing literature on the role of processed meats in NDDs. We concluded that intake of processed meat may have an adverse effect on NDDs.